PENGELOLAAN SAMPAH DI PASAR TRADISIONAL DESA KIAB JAYA KECAMATAN BANDAR SEI KIJANG KABUPATEN PELALAWAN - Zulmeliza Rasyid; Yessi Harnani; Beny Yulianto; Christine Vita Gloria Purba; Ida Robiyanti; M. Dedi Widodo (EcoNews, 2019)
In Government Regulation No. 81 of 2012 (regarding solid waste management), waste originating from daily activities in households that do not include feces and specific waste. Solid waste management is a systematic, comprehensive and sustainable activity that includes the reduction and handling of waste. The purpose of this study is to know the process of sorting, collecting, transporting, waste volume, financing, facilities, regulations and management.The method used is qualitative by conducting direct observations to the field and in-depth interviews to gain information about the solid waste management system from sorting, collecting and transporting waste in the Traditional Market of Kiab Jaya Village. The research subjects consisted of one market manager, two cleaners, two market traders and one buyer / community at the Kiab Jaya Traditional Market.The results of the study state that solid waste management in the Traditional Market of Kiab Jaya Village has not done good solid waste management, the sorting of wet waste is still stacked and scattered. The solid waste collection system on the market is done one to two times a week by janitors. There is no transportation of solid waste in the Traditional Market of Kiab Jaya Village, all dry solid waste is immediately burned and the wet one is left to stack until it is dry.